IMPLEMENTASI DISCOVERY LEARNING BERBASIS GEOGEBRA UNTUK MENINGKATKAN PEMAHAMAN KONSEP FUNGSI SISWA SMA - Siregar , Budi Halomoan; Munthe, Atiqah Shabirah; Najwa Dwi Heryanti; Br Sembiring , Ega Emeysadella; Br Tarigan , Alya Andani Rahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the learning conditions of functions and analyze the effectiveness of GeoGebra-assisted Discovery Learning in improving high school students' conceptual understanding. The study used a descriptive qualitative method, with data collection techniques including classroom observations, interviews with mathematics teachers, and documentation of 32 eleventh grade students. The results indicate that the use of GeoGebra increased student engagement through dynamic and interactive graphic visualizations, helping students explore the relationship between function equations and graph changes more clearly. Students appeared more active in discussions, were able to articulate conceptual reasoning, and demonstrated improvements in interpreting graphical and algebraic representations. The stages of Discovery Learning and the teacher's role as a facilitator also contributed significantly to the effectiveness of the learning. Overall, the integration of GeoGebra has been shown to support deeper conceptual understanding and has positive implications for the development of technology based mathematics learning.